Temperature distribution formulae-applications in photoacoustics - Maliński, M. (Archives of Acoustics, 2002)
This paper presents the new formula for the distribution of a periodical component of the temperature in the samples excited by the periodically modulated beam of light. It was shown that this formula enables the piezoelectric photoacoustic spectra analysis and interpretations. The influence of the backing material on the temperature distributions in the sample and piezoelectric photoacoustic spectra was presented and analyzed.